SAGITTAL AND VERTICAL CHARACTERISTICS OF DENTAL ARCH IN BOYS AND GIRLS WITH ORTHOGNATHIC BITE DEPENDING ON THE SHAPE OF HEAD AND TYPE FACE - Глушак, А.А. (World of Medicine and Biology, 2015)
Aim of our work - to establish normative values and features of sagittal and vertical characteristics of the dental arch in boys and girls with orthognathic bite depending on the shape of the head and face type. Materials and methods The primary indicator of the size of the teeth and head of 49 boys and 48 girls of Podillya with orthognathic bite derived from the database of SRC VNMU named after Pirogov. All of them made cephalometric study. Committee of bioethics Vinnitsa National Medical University named after Pirogov found that the studies are not contrary to the fundamental bioethical standards of the Helsinki Declaration, the European Convention on Human Rights and Biomedicine (1977), the relevant provisions of the WHO and the laws of Ukraine (protocol number 1 of 23.09.2003). In the sagittal plane were measured the following parameters of maxillary dental arch: canine maxillary sagittal distance; premolar maxillary sagittal distance; molar sagittal distance of the upper jaw. The same parameters were measured in the sagittal plane for the mandible dental arch. In the vertical plane the following parameters were measured of maxillary dental arch: depth of the palate at the level of canines; depth of the palate at the level of first small molar teeth; depth of the palate at the level of first large molar teeth. Head shape was determined by the formula ms_ms * 100 / g_op, where ms_ms - maximum width of the head; g_op - the maximum length of the head. Established the following distribution: boys dolichocephali c– 2, boys mesaticephalic – 13, boys brachycephalic – 17, boys hyperbrachycephalic - 17; girls dolichocephalic – 1, mesaticephalic girls – 13, girls brachycephalic – 16, girls hyperbrachycephalic - 18. Type of faces determined using morphological index of Garson - ratio of morphological face length to width face in the area of the zygomatic arches. Established the following distribution: boys with a very broad face – 11, boys with a broad face – 20, boys with a mean face – 13, boys with a narrow face – 4, boys with very narrow face - 1; girls with a very broad face – 15, girls with a wide face – 15, girls with a mean face – 14, girls with a narrow face - 4. Statistical analysis of the results was performed using the statistical software package "Statistica 5.5" using nonparametric methods. Results. Discussions In girls hyperbrachycephalic established statistically significant, or tendency to larger values size depth of palate at the level of canines and at the level of first small molar teeth than in meso- and hyperbrachycephalic; in boys with different forms of the head - statistically significant differences or trends of vertical characteristics of the dental arch is practically not installed (only larger depth of palate at the level of first small molar teeth in brachycephalic than in mesaticephalic). In boys with a broad face set statistically significant, or the tendency to lower values of palate depth size at the level of canines, at the level of first small and large molar teeth than in boys with a mean face as well as the depth of palate at the level of canines than in boys with a very broad face; girls with a mean face set only statistically significant smaller depth of palate at the level of canines than in representatives with other types of face. In boys and girls practically not found statistically significant sex differences of size sagittal and vertical characteristics of the dental arch.